PERANAN MOTIVASI SEBAGAI FAKTOR PENDORONG MINAT KUNJUNGAN WISATAWAN MANCANEGARA - Nasution, Mohamad Nur Afriliandi; Hendra Syaiful; Agung Edy; Frangky (JURNAL MENATA, 2022)
The purpose of this study is to explain the interest of tourists to come to Batam because of COVID-19, foreign tourist visits have increased again, but this has not been matched by the interest of tourists to return to religious tourist attractions, especially those in the Batam City Mosque. Through this research, an approach was carried out by looking at two different factors, firstly the push factors and pull factors for the arrival of these tourists, especially from international tourists. In this article the researcher only focuses on the driving factors, while the other factors will be a separate study supported by data after these driving factors are published. Through the driving factors for tourist arrivals, it can be explained that there are several important indicators that accompany it as encouragement, including educational, interpersonal, physiological, driving attractions, amenities, accessibility and additional services affecting foreign tourist tourism. The analysis of this research data uses a quantitative approach with explanatory methods. Sampling was carried out by accidental sampling method with intentional sampling technique. The sample used in this study has a 10% margin of error while the number of samples used is 102 respondents. The results showed that the driving factors of education, interpersonal, and physiological had a positive and significant effect on the interest of foreign tourists to return to religious tourism destinations for mosques in Batam City. What must be strengthened is the improvement of the completeness of the facilities for religious tourism activities.